Effect of multiple-injection strategies on diesel engine exhaust particle size and nanostructure. (November 2015) - Li, Xinling; Guan, Chun; Luo, Yueqi; Huang, Zhen
Abstract: Multiple-injection has been widely investigated to simultaneously reduce diesel NOx and soot emissions. While the comprehensive understanding of the effects of multiple injection on exhaust PM physical characteristics is still lacking. Three injection modes, single main, pilot-main and main-post injections, were compared in this work. The main objective is to better understand the influence of pilot and post injections on particle size and nanostructure characteristics in diesel exhaust. Experimental tests have shown that, for the pilot-main injection case, less premixed combustion and more diffusion combustion occur compared with the single main injection, which promotes formation of soot nuclei and results in a significant increase of number and mass of particles with the diameter above 100 nm. On the contrary, soot oxidation later in the combustion is improved due to the enhancement of gas mean temperature (GMT) and air/fuel mixing for the main-post injection case, which favors soot oxidation and leads to the decrease of particle number and diameter. A comparison of particle nanostructures for the pilot-main injection case and main-post injection case has been conducted, which indicates that both low in-cylinder temperature and relative short carbonization time lead to the particles of less carbonization level (short fringe length and large fringe tortuosity) for the pilot-main injection case. Particles exhibit highly ordered graphitic structure for the main-post injection case due to the increase of combustion duration and the enhancement of in-cylinder temperature during the later stage of combustion derived by post combustion, which presents potential negative effect on diesel particle filters (DPF) regeneration efficiency.